The Emotional Toll of Inflammatory Bowel Disease: Using Machine Learning to Analyze Online Community Forum Discourse. Issue 2 (2nd July 2019) - Lerrigo, Robert; Coffey, Johnny T R; Kravitz, Joshua L; Jadhav, Priyanka; Nikfarjam, Azadeh; Shah, Nigam H; Jurafsky, Dan; Sinha, Sidhartha R
Abstract: Background: Patients with inflammatory bowel disease are using online community forums (OCFs) to seek emotional support. The impact of OCFs on well-being and their emotional content are unknown. Methods: We used an unsupervised machine learning algorithm to identify the thematic content of 51, 591 public, online posts from the Crohn's & Colitis Foundation Community Forum. Results: We identified 10, 702 (20.8%) posts expressing: gratitude (40%), anxiety/fear (20.8%), empathy (18.2%), anger/frustration (13.4%), hope (13.2%), happiness (10.0%), sadness/depression (5.8%), shame/guilt (2.5%), and/or loneliness (2.5%). A common subtheme was the importance of fostering social support. Conclusions: High-throughput, machine learning-directed analysis of OCFs may help identify psychosocial impacts of inflammatory bowel disease on patients and their caregivers. Lay Summary: The Crohn's & Colitis Foundation Community Forum is a positive and supportive online group. People with a new inflammatory bowel disease diagnosis and people who need more support might find it helpful to join this online group.